Strategi Kepemimpinan Nasional Dalam Menyiapkan SDM Pemuda Menghadapi Bonus Demografi - Santoso, Bibit; Widiatmoko, Catur (Jurnal Wahana Bina Pemerintahan, 2017)
Indonesian youth is the future of the nation. Therefore, every Indonesian youth, who is still student, or who has completed his education, is an important actor who is very guaranteed to realize the ideals of the image of the life of our nation in the future.In various debates over the debate, there are always challenges, or challenges due to mistakes or mistakes that we make or do things that are outdoors that support our abilities, such as discussions about the natural situation or due to the financial crisis in the country others that affect us domestically. Demographic transition will change the age structure of the population, while the proportion of the young population (ages 0-14 years) increases, the proportion of the population of productive age (ages 15-64 years) increases rapidly, and the proportion of the population aged 66 years and over increases rapidly. DAFTAR PUSTAKAAnoraga Pandji. Psikologi Kepemimpinan Jakarta: Rineka Cipta.Aliminsya&Pandji,Kamus Istilah Manajemen, Bandung: CV Yarma Widya.Cravens David, 2001Pemasaran Strategis, Jakarta: Erlangga.Gitosundarmo Indiro & I Nyoman Sudita. 2000 Perilaku Keorganisasian Yogyakarta: BPFE.Goleman,Daniel.2003 Kepemimpi-nan Yang Mendatangkan Hasil. Yogyakarta: Amara Books.Winardi.2001. Kepemimpinan dalam Manajemen, Jakarta : Rineka CiptaLihat http://www.apindo.or.id/index.php/berita-a-artikel/news/927-pertumbuhan-kelas-menengah-dongkrak-ekonomi-ri-Hasil Susenas dan Penghitungan staf World Bank dalam Aviliani, dkk. 2011. Demographic Bonus dan Pertumbuhan Kelas Menengah. Bank Indonesia. 2011. Analisis Sensitivitas Konsumsi Rumah Tangga terhadap PDB danPengaruh Inflasi terhadap Pola Konsumsihttp://www.tempo.co/read/news/2012/09/13/090429281/Indonesia-Diminta-Waspada-Jebakan-Kelas-MenengahBank Indonesia. 2011. Informasi Kependudukan Indonesia.